2017
DOI: 10.1016/j.ajo.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography and Ultra-widefield Fluorescein Angiography for Early Detection of Adolescent Sickle Retinopathy

Abstract: Purpose Using standard screening techniques, sickle retinopathy reportedly occurs in 10% of adolescents with sickle cell disease (SCD). We performed a prospective, observational clinical study to determine if ultra-widefield fluorescein angiography (UWFA), spectral-domain optical coherence tomography (SD-OCT) and optical coherence tomography angiography (OCT-A) detect more frequent retinopathy in adolescents with SCD. Design Cross-sectional study. Methods Setting Institutional. Subjects Sixteen adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 29 publications
3
35
0
1
Order By: Relevance
“…Spectral-domain optical coherence tomography and optical coherence tomography angiography (SD-OCT and OCT-A) identified abnormal macular thinning and flow voids in the superficial and deep retinal capillary plexus in 20% of eyes that had been unobserved by biomicroscopy. These findings suggest that pediatric sickle retinopathy may be more prevalent than previously suspected [49,52]. Temporal macular thinning caused by paracentral acute middle maculopathy may be the result of occlusions at the level of the deep retinal capillary plexus (Fig.…”
Section: Subclinical Retinopathy and Recent Imaging Modalitiesmentioning
confidence: 78%
See 1 more Smart Citation
“…Spectral-domain optical coherence tomography and optical coherence tomography angiography (SD-OCT and OCT-A) identified abnormal macular thinning and flow voids in the superficial and deep retinal capillary plexus in 20% of eyes that had been unobserved by biomicroscopy. These findings suggest that pediatric sickle retinopathy may be more prevalent than previously suspected [49,52]. Temporal macular thinning caused by paracentral acute middle maculopathy may be the result of occlusions at the level of the deep retinal capillary plexus (Fig.…”
Section: Subclinical Retinopathy and Recent Imaging Modalitiesmentioning
confidence: 78%
“…Pahl et al conducted a crosssectional study in pediatric patients (age 10-19 years old) with SCD, demonstrating that all 24 eyes examined by UWFA had sickle cell retinopathy, even if this had not been detected on biomicroscopy. Findings included peripheral arterial occlusion in four of the 24 eyes and peripheral arteriovenous anastomoses in the remaining 20 eyes [49].…”
Section: Subclinical Retinopathy and Recent Imaging Modalitiesmentioning
confidence: 99%
“…10,11,[13][14][15]21,22 Published data are limited on acute and chronic complications, specifically associated with SCD in children prior to the time of transition to adult care. 13,20,[23][24][25][26][27] More information is needed about healthcare resource utilization (HCRU) and treatment patterns in young patients with SCD before they transition to adult care. 15,21,[28][29][30][31][32] Improved understanding of the HCRU in adolescents may help predict individuals at higher risk post-transition.…”
Section: Intr Introduc Oduction Tionmentioning
confidence: 99%
“…While comparing OCTA examination to traditional methods, previous studies have demonstrated that OCTA is a reliable tool for the analysis of retinal vasculature, similar to fluorescein angiography [21, 22], and that the retinal vasculature layers can be imaged more precisely compared to fluorescein angiography and indocyanine green angiography [23, 24]. With regard to glaucoma, HTG, after evaluation by OCTA, showed decreased peripapillary vessels that correlate with the RNFL and VF defects and impaired macular VD [9, 14, 17, 18, 25-28], while the OCTA evaluation in NTG subjects showed similar results and precision in the peripapillary and macular vasculature [10, 15, 17, 18, 29].…”
Section: Discussionmentioning
confidence: 99%